A smartphone app for intensive care unit rotation orientation - Bednarek, Olga; Loubani, Osama; Jessula, Samuel; Minor, Samuel (Canadian Medical Education Journal, 2020)
Implication Statement The Department of Critical Care at Dalhousie University developed a smartphone app to improve the quality of learner orientation to the intensive care unit (ICU). The app increased satisfaction with orientation and was perceived as useful. It was ranked as the second most valued resource for orientation after other residents. There is potential to improve the experience of learners with this popular technology.